Taṭwīr Takhṭīṭ al-Tadrīs li-al-Faṣl al-Dirāsī li-al-Kitābah al-Muqayyadah bi-Istikhdām CEFR min Khilāl al-Ta‘līm al-Mudammaj - Ramadhan Jabal Primadana; Muhammad Kamal bin Abdul Hakim; Syamsi Setiadi (Universitas Negeri Jakarta, 2020)
This study aims to produce a CEFR-based Semester Learning Plan (RPS) on guided writing (al-kitābah al-muqayyadah or Kitābah 1) course by using blended learning. This study uses a research and development method based on the ADDIE model (Analysis, Design, Development, Implementation) by limiting the stages to (1) need analysis of the fifth-semester students of Arabic Language Education Study Program, Universitas Negeri Jakarta in RPS of Kitābah 1; (2) design and development for RPS of Kitābah 1 which is adjusted to CEFR level A1 and blended learning; (3) product assessment conducted by expert reviewers. Based on the needs analysis obtained from data of 20 students, the need index for RPS of Kitābah 1 with blended learning models is 2.6 (on a scale of 1–3). RPS based on the CEFR for Kitābah 1 aims to make students have the ability to arrange words and phrases into simple sentences and write paragraphs in a guided manner. Finally, based on the expert’s assessment, the score was 4.19 (on a scale of 1–5) in the very good category. Thus, the RPS of Kitābah 1 can be developed and suitable for use.